Deaths Among Homeless in Ankara - Yağan, Murat; Koçak, Uğur; Demirel, Birol (The Bulletin of Legal Medicine, 2018)
Objective: Homeless people are a national problem for Turkey as well as in other countries. The higher death rates of homeless people than general population makes important to determine causes of preventable deaths and to inform the social institutions and the state about to take precautions against these deaths. Aim of this study is to build public attention to this problem, to make contribute to the statistical data about homeless people in our country and to obtain data in order to take preventive measures. Materials and Methods: In this study, autopsy reports of 127 homeless cases who died in Ankara and recorded by Morgue Department of Forensic Medicine Institution in Ankara between 1997-2006 were reviewed. The data were evaluated retrospectively in terms of age, gender, the place where the deceased was found, the season and the cause of death. The data obtained from the cases were recorded and analyzed by using the statistical program (SPSS 16.0). Results:It was found that 116 (91.33%) of homeless deaths were men and the most frequent deaths were between 30-61 years with a ratio of (70.08%). The places where they were found are mostly derelict buildings, construction sites and shielding places. Deaths mostly occurred in autumns and winters (62.99%). General hygiene of the found corpses of the homeless people (67.1 %) were distorted and autopsy was held for 42,51 % of total. It was determined that unnatural death causes (%55.11) were traffic accidents (14.17 %) and alcoholic intoxications (7.87%). Natural causes of deaths were found...